Pelatihan Peningkatan Kesadaran Keamanan Akun Digital Bagi Pelaku UMKM Desa Sawarna Banten - Prima Dina Atika; Aidah Afifah Hafshah; Fadia Amelia Putri; Rian Wijaya; Rifky Putra Wijaya; Zaki Nur Fauzan; Ridwan Nurfauzi; Rasyid Darusman; Muhammad Akmal Dzulfiqar; Mohamad Diandra Ferdiansyah; Septyo Saputro; Tedi Ramadhan (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The widespread expansion of digitalization has driven Micro, Small, and Medium Enterprise (MSME) owners in Sawarna Village to utilize various digital platforms for communication, marketing, and sales transactions. However, the high adoption rate of digital services is not matched by adequate understanding of account security, making MSME owners one of the most vulnerable groups to threats such as phishing, account hijacking, data misuse, and online fraud. Through the Community Service Program (KKN), this training activity was conducted to enhance awareness and capability of MSME owners in securing the digital accounts they use to support their business activities. The training encompassed socialization sessions, technical assistance, and basic audits of participants' account security settings. The results demonstrated an improvement in MSME owners' understanding of digital security risks as well as behavioral changes, particularly in the adoption of stronger passwords, activation of two-factor authentication, and configuration of account privacy settings. This program proves that KKN-based digital security training is effective in increasing awareness and digital account protection capabilities among MSME owners, thereby supporting the sustainability of their businesses in a more secure manner.